The Role of a Notary in the Establishment of a Limited Partnership After the Entry into force of the Electronically Integrated Business Licensing Service System According to Government Regulation Number 24 of 2018 - Tengku Yusuf Hanafiah Yovinanda; Adi Mansar; Ferry Susanto Limbong (PT FORMOSA CENDEKIA GLOBAL, 2022)
Over time, the Notary Profession in carrying out his profession, from what was only known as a scribe manually, then a typewriter, until now uses technology- and application-based facilities. Among them, the term Cyber Notary is known in America, and in Europe, the period E-Notary is known. Research Objectives To identify and analyze the role of a notary, legal consequences for the role of a notary and identify and analyze constraints and solutions in electronically integrated business licensing services in the process of processing, analyzing and utilizing data in this study using qualitative methods. Data analysis using qualitative analysis techniques. Empirical Legal Research (Sociological Juridical). This research is descriptive and analytical. The study found that a notary's role in electronically integrated business licensing services is related only to an assistance service in providing comprehensive services to business actors/communities related to applications for making permits. To be able to use (OSS), the Business Entity first takes care of validating the deed of establishment or amending the act through the SABU Online application. Then the data is registered to apply for a permit for the OSS system. Forms of Notary Liability If one day an error occurs in inputting data, the Notary cannot be prosecuted in civil, administrative or ethical terms as long as the Notary carries out his profession based on applicable regulations and clients based on their rights and obligations. Constraints and Solutions in Electronically Integrated Business Licensing Services are the lack of socialization between the one-stop service to the community, the lack of notification to the wider community or seminars related to One-Stop Integrated Services through applications (OSS), causing inequality in the online system that makes it easier Public. If the statutory provisions do not regulate or do not regulate, then the minister, heads of institutions, governors and regents/mayors have the authority to make decisions and take necessary actions to resolve the obstacles and problems referred to as long as they are following general principles of good governance. (OSS) is expected to make it easier for people to open businesses that legally have permits, thereby creating many jobs that can improve people's living standards and the country's per capita income